Identifikasi Senyawa Kimia Ekstrak Buah Naga Putih dan Pengaruhnya Terhadap Glukosa Darah Tikus Diabetes - WIBAWA, PUTU ALIT SURYA; ANTARA, MADE SUMA; DHARMAYUDA, OKA (Indonesia Medicus Veterinus, 2013)
This study aims to determine the class of chemical compounds ethanol extract of white dragon fruit (H. undatus) and the effect of decreasing blood glucose levels of male white rats (Rattus norvegicus) alloxan-induced. Blood samples were taken from 25 male white rats (R.norvegicus) aged 3 months with an average weight 150-300 grams. The design used was a completely randomized design (CRD) with five treatments of the mice given no treatment (negative control), rats treated with alloxan (positive control), rats treated with alloxan + ethanol extract of white flesh dragon fruit (H. undatus) 2% I-dose (50 mg / kg bw), rats treated with alloxan + ethanol extract of white dragon fruit (H. undatus) 2% II dose (100 mg / kg bw), rats treated with alloxan + glibenclamide 0.02% (a dose of 1 ml / kg bw). Each treatment examined blood glucose levels on days 0, 3, 7, 14, and 21. Before the adapted rats treated 2 weeks and fasted for 16-18 hours. Each treatment consisted of 5 replicates. The variables measured were blood glucose levels in each treatment. The data obtained was analyzed by using analysis of variance (ANOVA) and if there is a difference between treatments then proceed with testing on Duncan test. The research shows that ethanol extract of white dragon fruit (H. undatus) 2% dose (50 mg / kg bw), doses (100 mg / kg bw) and glibenclamide 0.02% 1 ml / kg body weight can significantly reduce levels blood glucose (P <0.05) day-7 until day 21 in alloxan-induced rats. This shows the ethanol extract of meat white dragon fruit (H.undatus) can be used as a lowering of blood glucose levels.